COEXISTENCE OF STANDARDIZED WIRELESS SYSTEMS IN THE 2.4 GHZ-ISM-BAND - Sikora, Axel; Groza, Voicu F. (International Journal of Computing, 2014)
Wireless systems continue to rapidly gain popularity. This is extremely true for data networks in the local and personal area, which are called WLAN and WPAN, respectively. However, most of those systems are working in the license-free industrial scientific medical (ISM) frequency bands, where neither resource planning nor bandwidth allocation can be guaranteed. To date, the most widespread systems in the 2.4 GHz ISM band are IEEE802.11 and Bluetooth, with ZigBee and IEEE802.15.4 as upcoming standards for short range wireless networks. In this paper we examine the mutual effects of these different communication standards. Measurements are performed with real-life equipment, in order to quantify coexistence issues.